Resiliensi Ekonomi Lokal Melalui Usaha Ikan Asap Pada Masa Pandemi Covid-19 - Nur Shinta Devayanti; Wahyu Eko Pujianto (Universitas 45 Surabaya, 2023)
This study aims to determine the defense of MSMEs and the development of the economic system during the Covid-19 pandemic. Micro, Small and Medium Enterprises are one of the largest contributors to Indonesia's Gross Domestic Product, so their existence is very beneficial for the workforce and the unemployed who need jobs. The scope of this research is Mrs. Siti's micro, small and medium business with the type of smoked grilled fish culinary business located in East Java, Balongdowo Pecis village, Candi Sidoarjo. This research method uses qualitative methods with stages of organizing decisions. From the results of research the Covid-19 pandemic has had an impact on decreasing sales, production volume, and decreasing income for MSMEs. Efforts during a pandemic, people take advantage of information technology and join market places, for the sake of continuity of work so that income continues. Community support in buying products from MSMEs also helps other communities as a mutual benefit.